Understanding the relationships between breastfeeding, malocclusion, ADHD, sleep-disordered breathing and traumatic dental injuries - SABUNCUOĞLU, OSMAN TALAT (CHURCHILL LIVINGSTONE, 2013)
Attention-deficit/hyperactivity disorder (ADHD), one of the most common neuropsychiatric disorders that present at young age, may occasionally be associated with physical problems and disorders. Among them exists a group of oral-pharyngeal conditions with considerable clinical morbidity. Previous research that identified absence or short duration of breastfeeding in ADHD children has been reviewed. Essential nutritional factors in breast milk can affect brain development and regulate the manifestation of ADHD symptoms. Low ferritin levels caused by insufficient breastfeeding may contribute to ADHD susceptibility because of the role of iron in dopaminergic activity. Insufficient breast feeding and subsequently excessive bottle-feeding may lead to increased rates of non-nutritive sucking habits, such as pacifier use and thumb-sucking, all of which are associated with the risk of development of malocclusions. Malocclusion refers to an unacceptable deviation from the ideal relationship of the upper and lower teeth and necessitates orthodontic treatment. Sleep-disordered breathing in children may present with neurocognitive symptoms that resemble ADHD and abnormal craniofacial developments, as well as malocclusions, have been cited as part of the syndrome. Obesity, which is an outcome of insufficient breastfeeding, is a shared comorbidity of ADHD and sleep-disordered breathing. The risk of traumatic dental injury is higher in children with ADHD and presence of malocclusions further increases the likelihood of dental injuries. In this review, certain oral-pharyngeal conditions relating to ADHD have been reviewed and links among them have been highlighted in a tentative explanatory model. More research that will provide increased awareness and clinical implications is needed. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: ATTENTION-DEFICIT/HYPERACTIVITY DISORDER; DEFICIT HYPERACTIVITY DISORDER; NONNUTRITIVE SUCKING HABITS; IRON-DEFICIENCY; RISK-FACTORS; CHILDREN; APNEA; PREVALENCE; DIAGNOSIS; SYMPTOMS